2019
DOI: 10.1177/1120700019858345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and dislocation rates after hip reconstruction using the Bioball system

Abstract: Introduction: Instability accounts for 1/3 of revision total hip arthroplasty (rTHA) performed in the UK. Removal of well-fixed femoral stems in rTHA is challenging with a risk of blood loss and iatrogenic damage to the femur. The Bioball universal adaptor (BUA), a modular head neck extension adaptor, provides a mechanism for optimisation of femoral offset, leg length and femoral anteversion. This can avoid the need for femoral stem revision in selected cases. The aim of this study is to present the clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(41 reference statements)
1
8
0
1
Order By: Relevance
“…Long-term outcomes on the use of the BioBall head neck adaptor for revision THA are limited. A recent study by Dabis et al 25 demonstrated good functional outcomes with a low dislocation rate in patients who had BioBall revision THA at 2-year follow-up. They included patients undergoing revision surgery for a variety of reasons and not just recurrent dislocation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Long-term outcomes on the use of the BioBall head neck adaptor for revision THA are limited. A recent study by Dabis et al 25 demonstrated good functional outcomes with a low dislocation rate in patients who had BioBall revision THA at 2-year follow-up. They included patients undergoing revision surgery for a variety of reasons and not just recurrent dislocation.…”
Section: Discussionmentioning
confidence: 96%
“…They included patients undergoing revision surgery for a variety of reasons and not just recurrent dislocation. Dabis et al 25 report a recurrent dislocation rate of 7% (2/28) with significant improvement in Euro-Quol (EQ-5D) Score ( p < 0.001), Oxford Hip Score ( p < 0.001) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores ( p < 0.001) following revision with Bioball. A recent meta-analysis on the Merete BioBall system by Novoa et al 24 demonstrated insufficient evidence to recommend or contradict the use of this system.…”
Section: Discussionmentioning
confidence: 99%
“…Some manufacturers also provide special ceramic heads for THA revision surgery, where the titanium sleeve is integrated into the ceramic head 62 and several studies have demonstrated good results when this technology is used. 63 68 …”
Section: Recommendationsmentioning
confidence: 99%
“…[9][10][11][12] In the event of inadequate femoral offset and/or length, rather than excessive anteversion or retroversion, the use of head adapters can allow length modularity to aid balancing soft-tissue tension with restoration of the proper geometry and biomechanics of the artificial hip. 13 The aim of this retrospective multi-centre study is to report on the results achieved with the use of head adapters in partial revision hip arthroplasty in avoiding instability of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of inadequate femoral offset and/or length, rather than excessive anteversion or retroversion, the use of head adapters can allow length modularity to aid balancing soft-tissue tension with restoration of the proper geometry and biomechanics of the artificial hip. 13…”
Section: Introductionmentioning
confidence: 99%